2013
DOI: 10.1002/ajh.23580
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab versus splenectomy in persistent or chronic adult primary immune thrombocytopenia: an adjusted comparison of mortality and morbidity

Abstract: Splenectomy and rituximab are both recommended as second-line treatment in immune thrombocytopenia (ITP), but they have never been directly compared. We compared their efficacy and serious adverse outcomes in a retrospective cohort of 105 adult primary ITP patients exposed to one or other of these treatments. Primary outcome was composite: death from hemorrhage or from infection and hospitalization for bleeding or for infection. Secondary outcomes were overall mortality, hospitalization for bleeding, hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 34 publications
0
44
0
1
Order By: Relevance
“…This long remission rates have been described in other series with similar long-term remission rates ranging from 60-80 % [21][22][23][24]. Thus, even in the presence of excellent remission rates with the use of anti-CD20 monoclonal antibodies such as rituximab, it is still debatable whether the use of such therapies are superior to splenectomy since monoclonal antibodies are also associated with risks such as infections [25,26]. The cost associated with the use of rituximab inhibits the widespread use of such drugs in developing countries, and hence, splenectomy is still a cheap but very effective option for patients with relapsed/refractory ITP.…”
Section: Discussionmentioning
confidence: 80%
“…This long remission rates have been described in other series with similar long-term remission rates ranging from 60-80 % [21][22][23][24]. Thus, even in the presence of excellent remission rates with the use of anti-CD20 monoclonal antibodies such as rituximab, it is still debatable whether the use of such therapies are superior to splenectomy since monoclonal antibodies are also associated with risks such as infections [25,26]. The cost associated with the use of rituximab inhibits the widespread use of such drugs in developing countries, and hence, splenectomy is still a cheap but very effective option for patients with relapsed/refractory ITP.…”
Section: Discussionmentioning
confidence: 80%
“…Splenectomy has been compared with rituximab in a retrospective data analysis. 13 The study revealed superior survival and durable remission in favor of splenectomy. However, due to its retrospective, non-randomized nature, the demographic data and comorbidity status between patients undergoing splenectomy and patients treated with rituximab were not balanced.…”
Section: Discussionmentioning
confidence: 93%
“…In modern clinical trials, TPO‐RAs have been compared with placebos or investigator defined “standard of care”, rather than specific second‐line treatment agents. Splenectomy has been compared with rituximab in a retrospective data analysis . The study revealed superior survival and durable remission in favor of splenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations